SISTEM UJI TAK RUSAK BERBASIS ULTRASONIK UNTUK KONTROL KUALITAS PADA FABRIKASI BATA TIMBAL - Rhakamerta Hijazi; Suprijanto; Freddy Haryanto; Ahmad Haerudin; Yusuf Giri Wijayaa; Jos Budi Sulistyo (Scientific Journal of Mechanical Engineering Kinematika, 2024)
BATAN has the authority to improve the quality of lead brick production, which is still fabricated conventionally. Therefore, a non-destructive testing system has been developed, consisting of a Partial Immersion Technique transducer used to maintain a perpendicular scanning angle due to the uneven surface of the lead brick, an un0rick board used for its flexibility and good capability in generating high-voltage electrical pulses and high sampling frequency, and a laptop. The result is the optimization of ultrasonic parameters, with a transducer frequency of 500 KHz and a pulse length of 0.5 Î¼s. Additionally, tests were conducted on three cases. A standard lead brick used as a reference has a propagation speed of 2.156 m/s. The lead brick with artificial defects had the first defect location estimated at 23.32 mm with an error of 16.62%, the second defect location estimated at 25.1 mm with an error of 0.44%, the third defect location estimated at 36.17 mm with an error of 9.57%, and the fourth defect location estimated at 9.38 mm with an error of 6.2%. The third case, a lead brick with natural defects, had the defect location estimated at 26.77 mm with an error of 1.08%.